Survey of Guanxi networks in business ventures to China - Deng, Feng (2009)
Guanxi is a product of Chinese culture. It is a major dynamics in Chinese society and refers to that special relationship which two persons and two groups of persons have with each other. This guanxi offers a business networking strategy for ventures in China and most importantly can generate trust between two parties. Theoretically seen it is possible that Chinese business relations are influenced by kinship or surname principles and associated solidarity. But it may not always be the case.